Kemakmuran dan Keaktifan Qatar Dalam Kancah Internasional - Arradya Pratama, Raghnal; Rini, Dwi Setyo; Arviani, Jannatul (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2023)
Qatar's profitable position in the oil and ga s market has radically changed its economy. This can be seen from the source of income for oil and gas export activities, which can earn an average per capita income of more than US 100,000, making it one of the richest countries in the world. Qatar is starting to play an international role through various sectors after its success in the global energy sector and gas governance. The focus of this research is to understand Qatar's prosperity in the international arena. The research method used is a qualitative research method with secondary data collection techniques through scientific writing, journals and news sites. Writing this article explains the investments made by Qatar in various countries in the world with Foreign Direct Investments (FDI) or foreign investment to 80 countries, Qatar's prosperity through Investment is also analyzed using the theory of Heckscher Ohlin with its superior natural resources, namely oil and natural gas can become the basis of Qatar's prosperity.